Surgical Management of Drug-Resistant Epilepsy through Corpus Callosotomy: Case Report and Literature Review - Bolzan, Nikolė; Mameniškienė, Rūta (Neurologijos seminarai, 2024)
Corpus callosotomy is a palliative surgical procedure used for a selected group of patients with Drug-Resistant Epilepsy (DRE) when antiepileptic drugs fail to achieve seizure control. While it significantly reduces seizure frequency, it does not cure epilepsy. In this article, we present the case of a 45-year-old man with DRE unresponsive to pharmacological treatment, who underwent a complete corpus callosotomy. Postoperatively, seizure frequency decreased by 80%, and functional independence improved, though some neurological deficits persisted. A systematic literature review was conducted on the role of corpus callosotomy in the treatment of epilepsy, patient selection criteria, clinical outcomes, and advances in surgical techniques. Future directions include minimally invasive approaches and neurostimulation therapy as complementary strategies for seizure management epilepsy.
Keywords: drug-resistant epilepsy; corpus callosotomy; seizure reduction; epilepsy surgery; neurostimulation